The significance of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in vestibular neuritis. (13th February 2015) - Chung, Jae Ho; Lim, Jonghyun; Jeong, Jin Hyeok; Kim, Kyung Rae; Park, Chul Won; Lee, Seung Hwan
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To investigate the significance of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in vestibular neuritis. Study Design Retrospective, case‐control study. Methods The study subjects were patients who received treatment for vestibular neuritis between January 2009 and December 2013, and a control group composed of 70 age‐ and sex‐matched healthy subjects who received laboratory testing as part of a routine health checkup. The subjects underwent a complete blood cell count and counts of the various cell subtypes to compare NLR and PLR in the vestibular neuritis patients and controls. The associations between laboratory test results and values of the vestibular function test and clinical information were examined. In addition, a subgroup analysis according to the duration of spontaneous nystagmus was performed. Results The mean NLR and PLR values of the patient group were significantly higher than those of the control group. Although caloric test outcomes and hospitalization period were not significantly correlated with blood profiles, the duration of dizziness needing antivertiginous drugs was positively correlated with NLR and PLR (P = .021, P = .020, respectively). In addition, NLR was negatively correlated with the length of time between symptom start and blood sampling (P = .005). The NLR and PLR value of patients with nystagmus for more than 5 days were significantly higher than those of patients whose nystagmus ceased within 5days. Conclusions This is the first report to evaluate the significance of NLR and PLR in vestibular neuritis. NLR and PLR should be taken into consideration as simple and reliable parameters for predicting the cause and severity of the disease. Level of Evidence 3b Laryngoscope, 125:E257–E261, 2015